NUTRITIONAL KNOWLEDGE FOCUSING ON WEIGHT CONTROL AMONG OFFICE PERSONNEL: A CASE STUDY OF ACADEMIC SUPPORT STAFF AT FACULTY OF SCIENCE AND FACULTY OF EDUCATION, SILPAKORN UNIVERSITY - Trakoon-osot, Wilai; Paenkaew, Benjawan; Kaewbut, Nantita; Intasupa, Uraiwan; Paobtip, Suvimon (Thai Bulletin of Pharmaceutical Sciences, 2018)
Being overweight and obese leads to non-communicable diseases and can affect quality of life. This study aimed to survey the nutritional knowledge, focusing on weight control, among academic support staff at the Faculty of Science and the Faculty of Education, Silpakorn University. There were 110 participants: 69 from the former faculty and 41 from the latter. The mean (SD) age was 42.3 (9.3) years. The majority of the participants (65.5%) had earned a bachelor degree or higher. This study revealed that, among the participants, 67.3% were overweight or obese, 50.9% were centrally obese, and 40% were undergoing weight reduction. The participants self-completed a questionnaire on nutritional knowledge related to weight control which consisted of 20 items. The median (IQR) of the knowledge score was 10.5 (3). Their nutritional knowledge was associated with their education level (p = 0.041) and gender (p = 0.034). Based on the large number of incorrect answers, the three most important nutritional aspects that should be addressed were the nutritive value of pumpkins (79.1%), mung beans (69.1%) and peanuts (65.5%). Another issue that should be rectified based on scientific evidence was “cold-pressed coconut oil and weight reduction”, which 63.6% replied incorrectly. Most participants (38.2%) indicated that social media was the most appropriate channel for providing health care information; therefore nutritional education about weight control by health professionals through this media appeared to be beneficial for office personnel.